Combined convective and viscous dissipation effects on peristaltic flow of Ellis fluid in non uniform tube (Journal of Naval Architecture and Marine Engineering, 2022)
Abstract:This paper investigates the peristaltic transport of Ellis fluid in a non-uniform tube with combined/individual effects of convective and viscous dissipation analytically. Low Reynolds number and long-wavelength approximation assumptions are considered in the analysis. An examination of the properties of the walls is also carried out. The expressions for velocity, temperature profile, and stream function are obtained subjected to convective boundary conditions. The peristaltic transport's significant characteristics are delineated with plots for various Ellis fluid parameter values. The viscous dissipation effects are found to be related to the Brinkman number, so it leads to rising fluid temperature in all cases.